Design and Comprehension Testing of Tailored Asthma Control Infographics for Adults with Persistent Asthma - Arcia, Adriana; George, Maureen; Lor, Maichou; Mangal, Sabrina; Bruzzese, Jean-Marie (Applied Clinical Informatics, 2019)
Background Adherence to daily inhaled corticosteroid medication is important for asthma control but low health literacy is a barrier to comprehension of control status and may contribute to medication nonadherence. Infographics tailored with patients' own data can support comprehension of health status, but these have not been applied to asthma successfully.Objectives This two-phased study developed and tested tailored infographics of (1) scores on the Asthma Control Questionnaire (ACQ), a self-report measure of symptom burden, and (2) pulmonary function test (PFT) results. The infographics are intended for use as communication and adherence-promotion tools in clinical interactions.Methods For both phases, participants (18+ years, English- or Spanish-speaking, persistent asthma) were recruited through two primary care clinics. In Phase I, we used a hybrid iterative participatory design process to refine prototype designs. In Phase II, we conducted individual comprehension assessment interviews with the finalized designs. Infographics were hand-tailored for each participant using their ACQ score and PFT results collected at the start of the interview. Two independent raters scored interview transcripts for gist and verbatim comprehension based on a predetermined rubric.Results The five Phase I design sessions led to final prototypes that participants (n = 21) considered appealing and easy to comprehend. All Phase II participants (n = 10) demonstrated complete gist and verbatim comprehension. Participants reacted favorably to receiving their information via infographics and expressed intentions to engage in self-management behaviors (e.g., medication adherence, smoking cessation, weight loss, and review of their care plan) in response to the information.Conclusion This study provides preliminary evidence that infographics can support comprehension of asthma control status and promote self-management intentions among adults with persistent asthma. Infographics can be programmed into electronic health records and/or standalone applications to allow for instant tailoring at the point of care.
Keywords: comprehension; visual aids; patient; consumer health; medication adherence; language/health literacy issues